Optimization study of preparation Iraqi grape seeds activated carbon for cadmium ion removal from aqueous solution - Jasim Mohammed Salman (Journal of Madenat Alelem University College, 2022)
Porous activated carbon prepared from Iraqi grape seeds (GS) using physical activation method, consisted of carbon dioxide (CO2) gasification. Based on the central composite design (CCD), two factor interaction (2FI) and quadratic models were respectively employed to correlate the activated carbon preparation variables. The effects of the activation temperature and activation time on the activated carbon yield and cadmium removal were investigated. From the analysis of variance (ANOVA), the most influential factor on each experimental design response was identified. The optimum conditions for preparing activated carbon from Iraqi grape seeds were found to be activation temperature of 237.38 oC and activation time of 0.58 h. The grape seeds activated carbon yield was found to be 19.94% while the removal of Cd (II) was found to be 86.85%.